Cholecystectomy via Kocher incision without peritoneal closure - Dorfman, Saul; Rincón, Alberto; Shortt, Hortensia (Investigación Clínica, 2013)
This investigation was carried out to evaluate the surgical wound outcome of patients who underwent cholecystectomy via Kocher incision, without peritoneal closure. Consecutive patients (n = 129) were randomized either to have the peritoneal closure (n = 66) or to have this step omitted (n= 63). Demographic data of the patients were similar in both groups. There were no significant differences in overall wound complication (p = 0.44), wound infection (p = 0.71), wound dehiscense (p = 0.96) and incisional hernia (p = 0.95). This study provides strong evidence that the avoidance of the peritoneal closure represents no adverse effect to the postoperative course of the patients.